2014
DOI: 10.1089/acm.2012.0774
|View full text |Cite
|
Sign up to set email alerts
|

Are the Effects of Community-Based Dance on Parkinson Disease Severity, Balance, and Functional Mobility Reduced with Time? A 2-Year Prospective Pilot Study

Abstract: "Are the effects of community-based dance on Parkinson disease severity, balance, and functional mobility reduced with time? A 2-year prospective pilot study." The Journal od Alternative and Complementary Medicine.20,10. 757-763. (2014 Results: There were no differences between groups at baseline. A significant group-by-time interaction (F [2,8] = 17.59; p < 0.0001) was noted for the MDS-UPDRS III, with the AT group having lower scores at 12 and 24 months than the controls. Significant interactions were also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
172
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 107 publications
(184 citation statements)
references
References 31 publications
9
172
0
3
Order By: Relevance
“…24 Every PD patient completed the assessment and intervention procedures during the ON medication period, with exception of those in two studies in which patients were enrolled in the intervention ON medication, but evaluated during the OFF medication period. 25,26 All the included studies reported some sort of improvement on gait related outcomes, whether significant findings regarded gait speed, stride length and time, step length, cadence or even performance on standardized measures (e.g. TUG).…”
Section: ■ Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…24 Every PD patient completed the assessment and intervention procedures during the ON medication period, with exception of those in two studies in which patients were enrolled in the intervention ON medication, but evaluated during the OFF medication period. 25,26 All the included studies reported some sort of improvement on gait related outcomes, whether significant findings regarded gait speed, stride length and time, step length, cadence or even performance on standardized measures (e.g. TUG).…”
Section: ■ Resultsmentioning
confidence: 99%
“…41 It is also important to highlight that some of the included studies reported significant findings on motor outcomes other than gait performance. Three studies found significant improvements in motor symptom severity in the training group in comparison to the control group, 25,26,29 while other three also reported significant changes in balance. 25,31 Thereby, it is important to explore whether gait performance enhancements are generalizable to more complex motor outcomes such as balance or if dual-task training also encompasses non-specific training effects which can even improve symptom severity in PD.…”
Section: 31mentioning
confidence: 99%
See 3 more Smart Citations